The vulnerability of refrigerated food to unstable power supplies. (September 2017) - Liddiard, Rob; Gowreesunker, Baboo (Lesh); Spataru, Catalina; Tomei, Julia; Huebner, Gesche
Abstract: This paper describes a simplified model for estimating the vulnerability to spoilage of a number of refrigerated foods in households, resulting from interruptions to the electricity power grid. The tool is demonstrated on a sample of three foods (milk, chicken and fish) in India, which historically has suffered significant interruptions. The effect of interruptions is quantified in terms of tonnage and monetary value of potential losses, in a number of simple scenarios. These losses are estimated for rural and urban areas of each Indian state. Our model indicates that extensions to the duration of power supply interruptions increases potential losses in domestic refrigerators, and that these losses are considerable when compared to losses expected in previous stages of the food supply chain. The current model's estimation of weight of food lost may be converted to a nutritional value, which opens an opportunity for new multidisciplinary areas of research.